Relationship between information access and public visiting the Indonesian National Library - Aini, Qurratu; Prijana, Prijana; Rodiah, Saleha; Sulaiman, Kabir Alabi (Universitas Padjadjaran, 2024)
Visiting interest comes as a form of fulfilling information needs in library. When users visit the library, they have an interest in obtaining a diverse information and ease of information access. Complete and reliable information is a tool in improving the library. High visitor interest can be an indicator of the library's successful development. This research aims to determine relationship between information access and public visiting the Indonesian National Library. The method used in this research is the survey method with a questionnaire as the research instrument on a sample size (n) of 510. The results showed that the information factors, people factors including gender and occupation, and the place factors have a significant association relationship with the public's interest in visiting the National Library of the Republic of Indonesia. The information factor got the highest result reaching 23.92%. Users factors including gender and occupation showed that 77.64% were women and 58.82% of visitors were students. The place factor obtained results with the majority of visitors agreeing that access to the National Library of the Republic of Indonesia is easy to reach as much as 96.66%. It can be said that the relationship between access to information and public interest in visiting the National Library of the Republic of Indonesia has an accepted hypothesis (H1). The conclusion shows that people have information access behavior of the Information Ground model with its three factors, namely, information, people, place.